Parental Acceptance of the COVID-19 Vaccine for Children Aged 6-11 Years: A Phenomenological Approach Based on the Health Belief Model (HBM) - Handayani, Eka Wuri; Dyah Aryani Perwitasari; Fredrick Dermawan Purba (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To analyze the factors in the acceptance of the COVID-19 vaccine among parents with children aged 6-11 years in Central Java. METHODOLOGY: This Descriptive phenomenology study was conducted in Central Java Province, with a sample of 20 parents from four sub-districts, from May to November 2025. Interview techniques were used to collect data by analyzing various components of the HBM. Thematic analysis was used to determine perceptions that influence vaccination decisions. RESULTS: The findings indicate that parents' perceptions of COVID-19 vaccination are generally high, which influences their decision to vaccinate their children. Influential factors include health conditions, misinformation, and psychological barriers. It was also found that social support from both family and healthcare professionals plays a significant role in vaccination decision-making. It was also found that Perceived Vulnerability, Severity, Perceived Barriers, Cues to Action, Perceived Benefits, and Self-Efficacy were significant. CONCLUSION: Health interventions are crucial for improving positive perceptions of vaccination's usefulness and reducing barriers that have a far-reaching impact on vaccination confidence.